Information Element of Inquiry-Based Education - McDaniel, Sarah; Vellardita, Lia; Wheeler, Diana (My University, 2009)
Presentation delivered at the May 2009 Teaching & Learning Symposium, Pyle Center, UW-Madison. Strategies for scaffolding disciplinary information skills into assignments and curriculae.
Keywords: assignment scaffolding; Integration of Information Literacy; Teaching and Learning Symposium; Inquiry learning